32-mm ceramic-on-ceramic total hip arthroplasty versus 28-mm ceramic bearings: 5- to 15-year follow-up study. Issue 1 (January 2019) - Higuchi, Yoshitoshi; Seki, Taisuke; Hasegawa, Yukiharu; Takegami, Yasuhiko; Morita, Daigo; Ishiguro, Naoki
Introduction: This study aimed to compare the clinical and radiographic results of 28-mm ceramic-on-ceramic (CoC) total hip arthroplasty (THA) to those of 32-mm CoC during a 5- to 15-year follow-up period. Methods: 107 joints (95 women and 6 men) underwent 28-mm CoC, and 60 (49 women and 7 men) underwent 32-mm CoC. The average patient age at the time of surgery was 56.1 and 55.7 years in the 28-mm and 32-mm CoC groups, respectively. Clinical and radiologic measurements of all patients were analysed. Results: The mean preoperative Harris hip score (HHS) was similar in the 2 groups (28-mm, 58.9; and 32-mm, 58.5). However, at final follow-up, the mean HHS of the 32-mm CoC (91.8) was significantly better than that of the 28-mm CoC (88.2) ( p = 0.003), as were the ranges of motion (ROM) for flexion (98.3 ± 13.5° vs. 87.3 ± 19.3°, p < 0.001) and abduction (27.8 ± 14.9° vs. 22.1 ± 19.3°, p = 0.007). The mean wear rate was 0.0044 mm/year for the 28-mm CoC and 0.0044 mm/year for the 32-mm CoC. No ceramic fractures were found in the 2 groups. One joint in the 28-mm CoC (0.9%) required revision owing to progressive osteolysis. Kaplan-Meier survival at 10 years, with implant loosening or revision THA as the endpoint, was 98.3% for 28-mm CoC and 100% for 32-mm CoC ( p = 0.465). Conclusion: There was no significant difference in ceramic-related complications between the 2 groups. Our study demonstrated that the 32-mm and 28-mm CoC are safe and are associated with good clinical outcomes.